Hyperkähler implosion and Nahm’s equations - Dancer, A; Kirwan, F; Roeser, M (Springer Berlin Heidelberg, 2015)
We use Nahm data to describe candidates for the universal hyperk¨ahler implosion with respect to a compact Lie group.